Annotated checklist and illustrated key to the species of Trichogramma Westwood (Hymenoptera: Trichogrammatidae) from South America - Querino, Ranyse B.; Zucchi, Roberto A. (Zootaxa, 2019)
A checklist is provided for all 43 species of Trichogramma recorded in South America, including diagnoses, comments, hosts, and distributions. A key to the South American species based on males (external morphology and genitalia) is also presented. Trichogramma koehleri Blanchard is here placed as species inquirenda.